Microdroplets: a sea of applications? - Huebner,A; Sharma,S; Srisa-Art,M; Hollfelder,F; Edel,JB; Demello,AJ (Lab Chip, 2008)
The exploitation of microdroplets produced within microfluidic environments has recently emerged as a new and exciting technological platform for applications within the chemical and biological sciences. Interest in microfluidic systems has been stimulated by a range of fundamental features that accompany system miniaturization. Such features include the ability to process and handle small volumes of fluid, improved analytical performance when compared to macroscale analogues, reduced instrumental footprints, low unit cost, facile integration of functional components and the exploitation of atypical fluid dynamics to control molecules in both time and space. Moreover, microfluidic systems that generate and utilize a stream of sub-nanolitre droplets dispersed within an immiscible continuous phase have the added advantage of allowing ultra-high throughput experimentation and being able to mimic conditions similar to that of a single cell (in terms of volume, pH, and salt concentration) thereby compartmentalizing biological and chemical reactions. This review provides an overview of methods for generating, controlling and manipulating droplets. Furthermore, we discuss key fields of use in which such systems may make a significant impact, with particular emphasis on novel applications in the biological and physical sciences.